2005
DOI: 10.1111/j.1523-1755.2005.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced bone mineral density in adults treated with high-dose corticosteroids for childhood nephrotic syndrome

Abstract: Adult survivors of childhood MCNS have a significant reduction in forearm trabecular vBMD, placing them at increased fracture risk at this site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 24 publications
4
45
1
Order By: Relevance
“…However, we did observe a decrease in BMD at the spine (a trabecular-rich site) but increased cortical thickness at the second metacarpal. Our results are therefore in line with previous reports [30,31] suggesting disparate effects of GCs on cortical and trabecular sites.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, we did observe a decrease in BMD at the spine (a trabecular-rich site) but increased cortical thickness at the second metacarpal. Our results are therefore in line with previous reports [30,31] suggesting disparate effects of GCs on cortical and trabecular sites.…”
Section: Discussionsupporting
confidence: 83%
“…Similar results were reported by Hegarty et al, who found by pQCT a significant reduction in distal radial trabecular volumetric BMD, but no reduction in total volumetric BMD in young adults who had NS during childhood [31]. We did not use pQCT to assess the effects GCs on the trabecular and cortical compartments separately.…”
Section: Discussionsupporting
confidence: 66%
“…Gulati et al [39] showed in a cohort of 88 children with idiopathic NS that spine BMD Z-scores were on average −1.6 SD below the healthy average at enrolment (at a mean of 3.2 ± 2.7 years following diagnosis) and remained low in the next 12 months. Hegarty et al [40] showed that LS BMD age-and gender-matched Z-scores were normal in adults who had received GC therapy for NS during the pediatric years, while LS BMD T-scores were reduced. The most striking finding in that report [40] was a persistently low distal radius trabecular volumetric BMD (by peripheral quantitative computed tomography (pQCT)) -on average almost a full standard deviation below the healthy average decades following the treatment of pediatric NS.…”
Section: Discussionmentioning
confidence: 99%
“…Hegarty et al [40] showed that LS BMD age-and gender-matched Z-scores were normal in adults who had received GC therapy for NS during the pediatric years, while LS BMD T-scores were reduced. The most striking finding in that report [40] was a persistently low distal radius trabecular volumetric BMD (by peripheral quantitative computed tomography (pQCT)) -on average almost a full standard deviation below the healthy average decades following the treatment of pediatric NS.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Leonard and colleagues (33,34) could not show significant deficits in BMC in 60 children aged 9.0 Ϯ 3.4 yr with glucocorticoid-sensitive NS, when correction was made for bone area, age, gender, race, and Tanner stage. Only one study dealt with adults who were treated for childhood NS: Hegarty et al (35) found in 34 adults a significantly decreased distal radial trabecular volumetric BMD (mean T score Ϫ1.04). The authors suggested that their method is the only correct way to measure BMC in patients with abnormal body size, which is often the case in patients who have used corticosteroids (35).…”
Section: Bone Mineral Densitymentioning
confidence: 99%